Literature Review: The Influence of Motivation, Work Discipline, Job Satisfaction, and Employee Loyalty on Employee Performance - Nurzanah, Eka; Damaiyanti, Alia (Nusantara Journal of Behavioral and Social Science, 2023)
The purpose of this article is to analyze the impact of motivation, work discipline, job satisfaction, and loyalty on employee performance based on five articles. This narrative literature review aims to identify and summarize previously published articles without critique of the reviewed articles. The type of research used in these five articles is quantitative. Employees are individuals capable of performing work, making them critically important as human resources for companies to support the achievement of set targets. This study has found a mutually positive relationship between variables. Among them, motivation affects employee performance, work discipline affects employee performance, job satisfaction affects employee performance, and work loyalty affects employee performance. This research has produced several reviews from five articles that have provided scientific decisions. The contribution of this research is expected to provide ease for other researchers who will develop their scientific work with similar themes in the future. Abstrak: Tujuan penulisan artikel ini adalah untuk menganalisis pengaruh motivasi, disiplin kerja, kepuasan kerja, dan loyalitas terhadap kinerja karyawan terhadap lima artikel. Narrative literature review ini bertujuan untuk mengidentifikasi dan meringkas artikel yang telah diterbitkan sebelumnya tanpa ada kritik untuk artikel yang direview. Jenis penelitian yang digunakan dalam 5 artikel ini adalah penelitian kuantitatif. Karyawan merupakan orang yang mampu melakukan pekerjaan, sehingga karyawan sangat penting sebagai sumber daya manusia bagi perusahaan untuk menunjang proses tercapainya target yang sudah ada.penelitian ini telah menemukan adanya hubungan yang saling berpengaruh positif antara variabel. Diantaranya motivasi berpengaruh kinerja karyawan, disiplin kerja berpengaruh terhadap kinerja karyawan, kepuasan kerja berpengaruh terhadap kinerja karyawan, dan loyalitas kerja berpengaruh terhadap kinerja karyawan. Penelitian ini telah menghasilkan beberapa kajian dari 5 artikel yang telah memberikan keputusan secara ilmiah. Kontribusi penelitian ini diharapkan dapat memberikan kemudahan bagi peneliti lain yang akan mengembangkan karya ilmiahnya dengan tema yang serupa dikemudian hari.